2015
DOI: 10.1128/mbio.01007-15
|View full text |Cite
|
Sign up to set email alerts
|

c-Type Cytochrome Assembly Is a Key Target of Copper Toxicity within the Bacterial Periplasm

Abstract: In the absence of a tight control of copper entrance into cells, bacteria have evolved different systems to control copper concentration within the cytoplasm and the periplasm. Central to these systems, the Cu+ ATPase CopA plays a major role in copper tolerance and translocates copper from the cytoplasm to the periplasm. The fate of copper in the periplasm varies among species. Copper can be sequestered, oxidized, or released outside the cells. Here we describe the identification of CopI, a periplasmic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…Mitochondria are important sites of utilization of both copper and iron. The biogenesis of CcO which is the final enzyme of the respiratory chain is one of the copper toxicity targets 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are important sites of utilization of both copper and iron. The biogenesis of CcO which is the final enzyme of the respiratory chain is one of the copper toxicity targets 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of this essential micronutrient can arise from defects in homeostasis or environmental exposures ( Bandmann et al., 2015 , Pena et al., 1999 , Renwick, 2006 ). Previously described molecular targets of Cu toxicity include cytochrome c biogenesis ( Durand et al., 2015 ), oxidative damage to cell constituents such as membrane lipids ( Howlett and Avery, 1997 ), nucleotide synthesis ( Johnson et al., 2015 ), and FeS-protein integrity or biogenesis ( Alhebshi et al., 2012 , Brancaccio et al., 2017 , Foster et al., 2014 , Macomber and Imlay, 2009 , Tan et al., 2017 ). Here, Yah1 proved to be a Cu-sensitive weak point of the FeS-cluster biogenesis/delivery pathway in yeast and, as expected for a key target ( Avery, 2011 ), disabling the protein produced Cu-sensitive phenotypes while overexpression of Yah1 or human Fdx2 conferred resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased activities also of complexes I, II, and III were described in cells with decreased Fdx2 content due to a mutation disrupting the ATG translation-initiation site, which is linked to mitochondrial myopathy ( Spiegel et al., 2014 ), and defects in respiratory chain complex activities are known to be associated with other human disorders ( Meunier et al., 2013 ). Therefore, besides downstream effects on Rli1, effects of Cu on respiratory chain function ( Djoko and McEwan, 2013 , Durand et al., 2015 , Hosseini et al., 2014 ) could also be partly mediated through its effects on mitochondrial ferredoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cu + , Ag + , or Cd 2+ can disrupt the solvent-exposed 4Fe-4S clusters of dehydratases ( 12 , 13 ). In the purple photosynthetic bacterium Rubrivivax gelatinosus , Cu + induces the expression of the CopA-ATPase and the periplasmic blue copper protein CopI ( 14 , 15 ). Recent in vivo studies showed that Cu + accumulation in R. gelatinosus and the human pathogen Neisseria gonorrhoeae Δ copA mutants affects cell growth by altering heme biosynthesis in the cytoplasm ( 14 , 16 ) or cytochrome c assembly in the periplasm for the Δ copI mutant in R. gelatinosus ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the purple photosynthetic bacterium Rubrivivax gelatinosus , Cu + induces the expression of the CopA-ATPase and the periplasmic blue copper protein CopI ( 14 , 15 ). Recent in vivo studies showed that Cu + accumulation in R. gelatinosus and the human pathogen Neisseria gonorrhoeae Δ copA mutants affects cell growth by altering heme biosynthesis in the cytoplasm ( 14 , 16 ) or cytochrome c assembly in the periplasm for the Δ copI mutant in R. gelatinosus ( 15 ). Interestingly, similar effect of tellurite on cytochrome c- type assembly was recently reported in Rhodobacter capsulatus ( 17 ).…”
Section: Introductionmentioning
confidence: 99%